2019
DOI: 10.1186/s12978-019-0676-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and causes of maternal mortality in Iran based on ICD-MM: a systematic review

Abstract: BackgroundNo systematic review has explored the causes of and factors associated with maternal mortality in the context of Iran. This study reviewed determinants and causes of maternal mortalities during pregnancy, delivery and the puerperium using the International Classification of Diseases-Maternal Mortality (ICD-MM), introduced by the World Health Organization.MethodsA systematic electronic search of all the studies that identified causes and/or determinants of maternal deaths in any part of Iran or in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 22 publications
(26 reference statements)
2
31
0
2
Order By: Relevance
“…Availability and provision of essential medicines including parenteral antibiotics, uterotonic drugs, parenteral anticonvulsants and anaesthetic drugs; and equipment including manual vacuum aspirators, vacuum extractor and set for basic neonatal resuscitation are therefore vital in addressing the direct causes of maternal and newborn deaths. Major direct causes of maternal deaths including infections, hypertensive disease in pregnancy and eclampsia, bleeding, obstructed labor, abortion complications (2,3) and causes of newborn deaths can be averted by providing Emergency Obstetric and Neonatal care (EmONC) (4).…”
Section: Imentioning
confidence: 99%
“…Availability and provision of essential medicines including parenteral antibiotics, uterotonic drugs, parenteral anticonvulsants and anaesthetic drugs; and equipment including manual vacuum aspirators, vacuum extractor and set for basic neonatal resuscitation are therefore vital in addressing the direct causes of maternal and newborn deaths. Major direct causes of maternal deaths including infections, hypertensive disease in pregnancy and eclampsia, bleeding, obstructed labor, abortion complications (2,3) and causes of newborn deaths can be averted by providing Emergency Obstetric and Neonatal care (EmONC) (4).…”
Section: Imentioning
confidence: 99%
“…Although this is considered to be a remarkable success, it will be very di cult to maintain and improve these indicators since, according to the Sustainable Development Goals, this gure should be reduced to the ratio of 9 deaths per 100,000 by 2030. Accordingly, there is a need for more effort and interventions beyond existing programs [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, one of the most important goals of the Ministry of Health and Medical Education to maintain and improve this index is to prevent the recurrence of repetitious deaths, that is, the repeatable accidents under the same circumstances that, despite the constant efforts of the experts, have not been successfully achieved [7]; so that, bleeding and hypertension have been for many years the leading causes of maternal deaths throughout the country, even in the more bene ted provinces [8]. Thus, although the maternal mortality rate is acceptable and even less than the world average, the causes of deaths are still worrisome that is due to the fact that they are highly preventable and, thus, their prevalence is unacceptable [9].…”
Section: Introductionmentioning
confidence: 99%
“…In 9(17%) cases, death occurred in the postpartum period. The characteristics of postpartum deaths are presented in Table 2. A recent comprehensive meta-analysis suggested that 20.6% of pregnancy-related deaths in Iran have been due to direct causes [6]. Another national study also demonstrated that indirect causes accounted for 36.7% of maternal mortalities during 2009-2012 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among non-obstetrical death causes in our study, cardiac diseases were the most prevalent ones; 1 out of 5 deaths were due to cardiac disease. Previous reports also recognized cardiac diseases as the most frequent indirect cause of death in pregnant women [6,7]. Commonly, cardiovascular diseases are disregarded during the routine care of pregnant women (even in developed countries), and screening programs for cardiac diseases are strongly recommended during pregnancy [14].…”
Section: Introductionmentioning
confidence: 99%